HYPERNATREMIC DEHYDRATION AND ACUTE MASSIVE PULMONARY EMBOLISM: COINCIDENCE OR TRUE RISK FACTOR - Zulkufli, Muhamad Razi (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Diabetes Insipidus (DI) is a common complication after extensive transcranial surgery for craniopharyngioma. DI mainly causes impairment of the sense of thirst and vasopressin (AVP) secretion. This puts the patient at risk of severe dehydration and hypernatremia. Venous thromboembolism is one of the potentially fatal complications which can occur due to severe dehydration and hypernatremia. CASE We report a 22-year-old Malay male, college student, with underlying panhypopituitarism and chronic diabetes insipidus post-removal of craniopharyngioma at the age of 8 years with acute massive bilateral pulmonary embolism (PE). He presented to our Emergency Department with acute onset of shortness of breath and chest pain for a day. Although feeling unwell, he was still able to ambulate and attend school. One day PTA, due to poor oral intake, he did not take his replacement therapy tablets: hydrocortisone, L- thyroxine and desmopressin. Upon arrival, he was noted to be hypotensive with a blood pressure of 70/50 mmHg and a heart rate of 110 bpm. His O2 saturation at room air was 80%. He appeared to be dehydrated with dry tongue. His GCS on arrival was E3V5M6. The abnormalities of his blood investigations were urea of 6.4 mmol/L, creatinine of 292 umol/L and sodium of 150 mmol/L. ECG showed sinus tachycardia with features of acute right ventricular strain pattern with S1Q3T3. Bedside echocardiogram showed features of acute PE with a dilated right ventricle and the presence of McConnell’s’ sign. A CTPA showed evidence of bilateral main pulmonary artery saddle embolism with RV thrombus. He was then referred to the National Heart Institute (IJN) for EKOS and catheter-guided thrombolysis where he was successfully treated. CONCLUSION The case illustrates the importance of severe hypernatremia and dehydration as predisposing factors for venous thromboembolism.